Enhancing The Inherent Coping Mechanism of Teachers in The Course of Health and Security Crisis - Galleposo, Gabriel T. (EduLine: Journal of Education and Learning Innovation, 2021)
There is a limited number of studies on why people, specifically teachers, can immediately cope with health and security crisis, and continue to live their lives as normally as those who have not experienced such events in their lives, hence, the necessity to conduct this study. It explored the factors that influenced their coping mechanisms through exploratory sequential mixed method, involving respondents from seven schools district of Zamboanga Sibugay Division and from one school district of Lanao del Sur. The qualitative data gathered from 10 respondents through face-to-face interview and focused group discussion arrived at the factors that influenced the inherent coping mechanisms, namely: family, faith, profession, alliance, self-reliance, and service. The quantitative data gathered from 131 respondents through a researcher-made survey instrument were subjected to Pearson coefficient of correlation, t-test, weighted mean, and stepwise regression. It is concluded that faith, family, alliance, and profession wield a significant influence in the coping mechanisms of the respondents. Experience, and training were also found to have a differentiating performance in coping from health and security crisis; and that success in coping from catastrophic situations depends greatly on these factors. This study further proposed a model which can be used as basis in designing mental, spiritual, emotional, and social health programs to enhance the inherent coping mechanisms of teachers.